Enhancing patient satisfaction and reducing nurse workload: the impact of multimedia health education in a prospective single-center randomized controlled trial - Yang, Liping; Qin, Zilan; Yao, Jia; Xu, Huan; Tian, Jinhui; Ren, Yanxian; Wang, Haiping; Meng, Wenbo (Frontiers in Medicine, 2025)
IntroductionHealth education is an important part of nursing care. Verbal health education is a common practice in surgical wards, which is time-consuming and laborious. Thus, this study aims to evaluate whether multimedia health education reduces nurses’ workload without compromising patient and family satisfaction in a surgical context.MethodsWe conducted a parallel-group, prospective randomized controlled trial at the Hepatobiliary Surgery Institute of Lanzhou University’s First Hospital between July 2019 and May 2022. Eligible patients (≥18 years) with general surgical conditions and acceptable for surgery were randomly assigned (1:1) to receive a multi-media health education group or a standard health education group. Randomization was performed by an independent statistician using a computer-generated randomization list. The nurses’ workload and satisfaction were the main outcomes; the anxiety level of patients and the variables affecting nurse workload were the secondary outcomes.ResultsA total of 184 eligible participants were randomly assigned to receive multimedia health education and standard health education. The results showed that multimedia health education can shorten the time [15.21 (0.63)vs.16.94 (3.96)] nurses spend on health education during patient admissions, the difference being statistically significant (p < 0.001), but it did not lower the satisfaction levels of nurses [73.46 (2.36) vs. 67.16 (5.52)], patients [53.35 (2.09) vs. 47.86 (5.00)], their families [53.35 (2.28) vs. 47.86 (4.53)] and doctors [73.33 (2.40) vs. 68.07 (4.92)] regarding health education (p < 0.001); in fact, it increased their satisfaction.ConclusionMulti-media health education could reduce nurses’ workload and enhance patient satisfaction but not increase complications.Clinical trial registrationhttps://www.clinicaltrials.gov/, identifier [NCT03989401].